2008
DOI: 10.1074/jbc.m807268200
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Surfactant Protein D Inhibits Lipopolysaccharide (LPS)-induced Inflammatory Cell Responses by Altering LPS Binding to Its Receptors

Abstract: Pulmonary surfactant protein D (SP-D) 3 is a member of the collectin protein family that also includes surfactant protein A (SP-A) and mannose binding lectin (1, 2). The structure of the collectins is characterized by four domains consisting of: 1) an N terminus involved in interchain disulfide bonding, 2) a collagen-like domain, 3) a coiled-coil neck domain, and 4) a carbohydrate recognition domain (CRD) (3). SP-A and mannose binding lectin contain collagenous domains consisting of 23 and 19 repeating Gly-X-Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
79
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 41 publications
0
79
0
Order By: Relevance
“…8,9 In addition, SP-D interacts with the other pattern-recognition molecules including Toll-like receptors (TLRs) and TLR-associated molecules CD14 and MD-2, and regulates inflammatory responses. [10][11][12] It has been suggested that SP-D expression levels are inversely correlated with lung cancer progression. The genetic abnormalities in SP-D were associated with lung cancer pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 In addition, SP-D interacts with the other pattern-recognition molecules including Toll-like receptors (TLRs) and TLR-associated molecules CD14 and MD-2, and regulates inflammatory responses. [10][11][12] It has been suggested that SP-D expression levels are inversely correlated with lung cancer progression. The genetic abnormalities in SP-D were associated with lung cancer pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, these are trimeric subunits stabilized by disulfide bonds; subsequently higher-order multimers produce a wheel-like dodecameric structure stabilized by interchain sulfhydryl bonds (37,38). SP-D structure is critical to its function (39). Although the carbohydrate recognition domain mediates its interactions with pathogens, several in vivo studies in which mutant or full-length SP-D were expressed in Sftpd 2/2 mice lungs suggest that the full function of SP-D is dependent on a full-length, multimeric protein (40)(41)(42)(43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…The second is a modulatory effect on signal transduction. SP-D interacts with the extracellular domains of TLR4, TLR2, MD2, and the complex of TLR4-MD2 via its CRD (25,28,34). SP-D can inhibit LPSinduced signal transduction via TLRs independent of the presence of TLR ligands (34).…”
Section: Discussionmentioning
confidence: 99%